Meaning in the Weaving: Mapping and Texture as Figures of Spatiality and Eventness - Paavolainen, Teemu (Nordic Theatre Studies, 2015)
Advocating a dramaturgical ontology of events rather than objects – or ecologies rather than cartographies – the article defends the metaphors of texture and weaving as intuitive, non-anthropocentric alternatives to current idioms of becoming and emergence. Already popularized as the very definition of “dramaturgy” by Eugenio Barba, these are specifically traced through Tim Ingold’s recent anthropology of weaving and S. C. Pepper’s philosophical pragmatism: where Ingold’s ecology of lines admits to “no insides or outsides [...] trailing loose ends in every direction”, Pepper’s “contextualistic world” of events admits “no top nor bottom” to its strands and textures. Intended only as a theoretical introduction to the implications of a certain family of metaphors (complete with a graphic representation thereof ), this article distinguishes the eventness of texture from certain notions of spatial “mapping” and discusses the “ecological” range of the metaphor through the concepts of textural fusion and spread.